HUBUNGAN TINGKAT PENDIDIKAN, PEKERJAAN DAN DUKUNGAN KELUARGA TERHADAP PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG PADA WANITA USIA SUBUR DI KLINIK BPJS IRMA SOLIKIN MRANGGEN DEMAK - Sherli Deviana; Widya Mariyana; Rinda Intan Sari (Pusat Riset dan Inovasi Nasional, 2023)
The Long-Term Contraception Method is an effective and efficient method to manage the pregnancy and stop the pregnancy of a fertile couple that does not want to have babies. This method is useful for the long-term duration, 10 years ahead. The selection of contraception tools receives various factors, such as socio- demographical factors: education, age, job, and the number of children. This research determined the correlation between education, profession, and family support toward the long-term contraception method selection for fertile women. This analytical survey research used a cross-sectional design. The population consisted of fertile women with active contraception acceptors at the BPJS Clinic, Irma Solikhin, consisting 201 people. The applied sampling technique was purposive sampling. The obtained sample was 134 respondents. The applied instrument was a questionnaire. The applied data analysis technique was Chi-square. The results showed a correlation between education and the selection of the Long-Term Contraception Method with a p-value of 0.000, lower than 0.05. The result showed a correlation between profession and the Long-Term Contraception Method at the clinic with a p-value of 0.000, lower than 0.05. The same result was also observable in the family support toward the Long-Term Contraception Method with a p-value of 0.000, lower than 0.05. Keywords: Education, Profession, Family Support, LTCM